Exploring unregulated substance use health data in Ontario, Canada: Identifying gaps, addressing challenges, and uncovering opportunities - Ali, Farihah; Law, Justine; Russell, Cayley; Imtiaz, Sameer; Bayoumi, Ahmed; Werb, Dan; Rehm, Jürgen (Frontiers in Public Health, 2025)
Canada’s overdose epidemic underscores the urgent need for high-quality, comprehensive, and timely national health data to inform evidence-based policies, population health management, and targeted intervention strategies. Using the province of Ontario, Canada, as a case study, this paper examines the current landscape of unregulated substance use health data, including both administrative and non-administrative health data sources. Health data on unregulated substance use in Ontario are fragmented, inconsistently collected, and poorly shared across organizations and jurisdictions. This creates significant barriers for researchers and decision makers in accessing timely and reliable information. Moreover, significant gaps persist in key areas, including prevalence estimates, treatment uptake, drug use profiles, marginalized populations, and disaggregated socio-demographic data. These deficiencies reflect and compound limitations at the national level, and hinder comprehensive analyses and informed decision-making, as well as progress toward coordinated national surveillance. To address these challenges, we propose several key recommendations: (1) standardize and integrate data to enhance consistency and interoperability among data sources; (2) improve data availability and accuracy to strengthen reporting mechanisms, increase transparency, and enable real-time monitoring of substance use trends, and (3) reduce barriers to data collection, analysis, and dissemination through enhanced collaboration and innovation. These strategies will improve provincial response efforts and contribute to building a national surveillance system that supports evidence-based decision-making to more effectively address the overdose crisis.